Development of Audio Visual-Based Quran Reading Training Media at the Quran House in Padangsidimpuan City - Hilman Rizky Hasibuan; Zulhimma Zulhimma; Muhammad Roihan Daulay (Yayasan Zia Salsabila, 2026)
This research was motivated by the still low ability of students to recite nagham independently and the use of learning media that are still simple and only audio-based without visualization of tone patterns and vocal techniques. This study aims to develop an audio-visual based training media for the art of Qur’anic recitation that is valid, practical, and effective in improving the tilawah abilities of students at Rumah Qur’an Kota Padangsidimpuan. The research method used was Research and Development (R&D) with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through observation, interviews, questionnaires, documentation, and tilawah ability tests. The results of the study showed that the developed media achieved a very valid level of validity, with media expert validation scores of 90%, material expert scores of 92%, and learning expert scores of 96%. The practicality level obtained scores of 80% and 95.5%, categorized as practical and very practical, while the effectiveness level obtained a student response score of 89%. Therefore, the audio-visual based training media for the art of Qur’anic recitation was declared feasible, practical, and effective for use in learning Qur’anic tilawah.